First record of subgenus Thao Tsuneki, 1982 (Hymenoptera: Crabronidae: Crabronini) from India: a new subspecies and a key to all subspecies of Crossocerus (Thao) nitidicorpus Tsuneki - Saini, Varun; Dey, Debjani (Zootaxa, 2022)
The subgenus Thao Tsuneki, 1982 of the genus Crossocerus Lepeletier de Saint Fargeau and Brullé, 1835 is recorded for the first time from India. A new subspecies viz., Crossocerus (Thao) nitidicorpus indicus, (India: Uttarakhand) is described. A key to all subspecies in the subgenus Thao is provided.